Studi Kapasitas Saluran Drainase pada Area Depan SPBU Mahkota Jalan Kapten Soedjono Kecamatan Sambutan Samarinda - Oktaviani, Viva; Tohir, Musrifah; Suharto, Harto (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the capacity of drainage channels in the Front Area of the Mahkota Petrol Station on Jalan Kapten Soedjono, Sambutan District, whether it is able to accommodate the surface flow discharge that occurs due to rain. The methods used include direct surveys in the field, rainfall data collection, channel geometric data, and hydrological and hydraulic analysis using rational methods and Manning equations. The results showed that some channels at the study site had a smaller capacity than the maximum runoff discharge that occurred, so it had the potential to cause local inundation and flooding. The maximum daily rainfall data for 10 years was analyzed using the distribution of Pearson Log Type III with the planned rainfall of 2 years of the 2-year re-period of 107.09 mm. The planned flood discharge (Qt) was calculated using a rational method, with a result of 1,447 m³/second (right channel) and a concentration time of 0.150 hours. The capacity of the channel with right dimensions (a: 1.40 m, b: 1 m, h: 1 m) of 2.117 m³/s, indicates that the channel is capable of accommodating the design discharge. However, the results of field observations indicate the need for replanning to maintain smooth flow and prevent potential local inundation. This research can be the basis for improving the drainage system in Samarinda City.